Identification and Functional Analysis of Long Intergenic Non-coding RNAs Underlying Intramuscular Fat Content in Pigs - Zou, Cheng; Li, Long; Cheng, Xiaofang; Li, Cencen; Fu, Yuhua; Fang, Chengchi; Li, Changchun (Frontiers in Genetics, 2018)
Intramuscular fat (IMF) content is an important trait that can affect pork quality. Previous studies have identified many genes that can regulate IMF. Long intergenic noncoding RNAs (lincRNAs) are emerging as key regulators in various biological processes. However, lincRNAs related to IMF in pig are largely unknown, and the mechanisms by which they regulate IMF are yet to be elucidated. Here we reconstructed 105,687 transcripts and identified 1,032 lincRNAs in pig longissimus dorsi muscle (LDM) of four stages with different IMF contents based on published RNA-seq. These lincRNAs show typical characteristics such as shorter length and lower expression compared with protein-coding genes. Combined with methylation data, we found that both the promoter and genebody methylation of lincRNAs can negatively regulate lincRNA expression. We found that lincRNAs exhibit high correlation with their protein-coding neighbors in expression. Co-expression network analysis resulted in eight stage-specific modules, gene ontology and pathway analysis of them suggested that some lincRNAs were involved in IMF-related processes, such as fatty acid metabolism and peroxisome proliferator-activated receptor signaling pathway. Furthermore, we identified hub lincRNAs and found six of them may play important roles in IMF development. This work detailed some lincRNAs which may affect of IMF development in pig, and facilitated future research on these lincRNAs and molecular assisted breeding for pig.